Prevalence and determinants of poor sleep quality and depression among postpartum women: a community-based study in Ramechhap district, Nepal. Issue 2 (11th July 2019) - Khadka, Roshan; Hong, Seo Ah; Chang, Yan-Shing
Abstract: Background: Due to the limited number of studies in low- and middle-income countries (LMICs), this study aimed to identify the prevalence and determinants of postpartum poor maternal sleep and depression. Methods: This cross-sectional study was conducted with 380 women who were 2–12 months postpartum in March and April 2017 in Ramechhap district, Nepal. Multiple logistic regression was used to identify the associated factors. Results: The prevalence of poor sleep quality and depression was 28.2% and 18.7%, respectively. Poor sleep quality was associated with having an occupation (in government or business, odds ratio [OR] 6.69; in agriculture/labour, OR 15.5), a male infant (OR 2.37), home delivery (OR 2.17), mental illness during pregnancy (OR 5.87), complications after delivery (OR 5.58) and postpartum depression (OR 2.86). Meanwhile, postpartum depression was associated with having no post-natal care (OR 98.7), living in a nuclear family (OR 48.5), living in a rural area (OR 26.6), having a male infant (OR 4.61), having complications after delivery (OR 21.9), introducing complementary foods before 6 months of age (OR 4.71) and having poor sleep quality (OR 3.20). Conclusions: A relatively high prevalence of depression and poor sleep quality were found. The close positive association between poor sleep quality and depression suggests the need for early identification and support for women at risk of poor sleep quality and depression in Nepal.